Estudo sobre os aspectos culturais da terminologia dos contratos de prestação de serviços em língua portuguesa e língua francesa - Pandim, Gildaris Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This work, inserted in the scope of Terminology, aims at studying the recurrent terminology in service agreements in the language pair Portuguese (from Brazil) and French (from France). The subject matter of this legal instrument is the performance of material or intellectual services upon remuneration and can be executed between individuals and legal entities. Regarding the General Terminolgy, we relied on the theoretical frameworks developed by Barros (2004, 2007), Depecker (1999, 2002, 2005) and Rey (1979, 1988, 2007). Also, with respect to the Bilingual Terminology, we based ourselves on the researches developed by Barros and Silva (2005), Depecker (2002) and Dubuc (2002). Finally, the study on cultural factors has been based on the works from Boulanger (1995), Diki-kidiri (1998, 2007, 2008), Gambier (1987), Gaudin (1991, 1993, 2003, 2007) and Guespin (1985). The research was carried out based on two study corpora, comprised of agreements originally drafted in Portuguese (CPSP) and by agreements originally drafted in French (CPSF). The collection of the corpora followed specific criteria related to language, to the environment (writing documents), to gender (professional and specialized), to the authorship and to the date and place of publication, and the agreements comprising the corpora have been gathered from several sources: virtual especially (websites of companies, law firms, accounting firms), a Brazilian law firm, a French law firm and a French-Brazilian law firm. From the perspective of terminological studies, terminology found in service agreements consist of simple terms, complex terms, compound terms, brachygraphic forms (abbreviations and acronyms). Once they are legal instruments, service agreements contain many terms arising from the legal field. From the interlinguistic perspective, a large part of the terms (80%) has counterparts in the language pair Portuguese-French with similar concept, ...

Ce travail s’insérant dans le domaine de la Terminologie a comme objectif l’étude de la terminologie présente dans le contrat de prestation de services en portugais (du Brésil) et en français (de France). Ce document juridique a pour objet la réalisation de services matériels ou intellectuels, moyennant rémunération et il peut être conclu entre des personnes physiques et des personnes morales. Nous nous sommes basées sur les approches théoriques développées par Barros (2004, 2007), par Depecker (1999, 2002, 2005) et par Rey (1979, 1988, 2007) en ce qui concerne la Terminologie générale. Nous nous sommes basées, de plus, sur les recherches tenues par Barros e Silva (2005), par Depecker (2002) et Dubuc (2002) pour la Terminologie Bilingue. Enfin, l’étude des aspects culturels a été réalisé en ayant comme repère les travaux de Boulanger (1995), de Diki-kidiri (1998, 2007, 2008), de Gambier (1987), de Gaudin (1991, 1993, 2003, 2007) et de Guespin (1985). Les recherches ont été réalisées à partir de deux corpus d’étude, composés de contrats rédigés originellement en langue portugaise et de contrats rédigés originellement en langue française. La procédure de repérage des corpus a été réalisée en suivant des critères spécifiques concernant la langue, la nature (documents écrits), le genre (professionnel et spécialisé), la source et la date et le lieu de publication. Les contrats ayant composé les corpus sont issus de différentes sources, électronique principalement (sites Internet d’entreprises, cabinets d’avocats, cabinets de comptabilité), ainsi que un cabinet d’avocats brésilien, un cabinet d’avocats français et un cabinet d’avocats franco-brésilien. La terminologie repérée dans les contrats de prestation de services dispose, du point de vue des études terminologiques, de termes simples, de termes complexes, de termes composés, d’abréviations (sigles et acronymes) ...

O presente trabalho, inserido no âmbito da Terminologia, tem como objetivo o estudo da terminologia recorrente em contratos de prestação de serviços no par de línguas português (do Brasil) e francês (da França). Para isso, valemo-nos dos aspectos teóricos do contrato de prestação de serviços no Brasil e na França, regido pelo Código Civil em ambos os países. Esse documento jurídico tem por objeto a realização de serviços materiais ou intelectuais mediante remuneração e pode ser firmado entre pessoas físicas e jurídicas. Baseamo-nos nos pressupostos teóricos desenvolvidos por Barros (2004, 2007), por Depecker (1999, 2002, 2005) e por Rey (1979, 1988, 2007) no que concerne à Terminologia Geral. Fundamentamo-nos, ainda, nas pesquisas desenvolvidas por Barros e Silva (2005), por Depecker (2002) e Dubuc (2002) no que diz respeito à Terminologie Bilíngue. Por fim, o estudo de aspectos culturais foi baseado nos trabalhos de Boulanger (1995), de Diki-kidiri (1998, 2007, 2008), de Gambier (1987), de Gaudin (1991, 1993, 2003, 2007) e de Guespin (1985). O levantamento dos termos foi realizado com base em dois córpus de estudo, compostos de contratos originalmente redigidos em língua portuguesa (CPSP) e de contratos originalmente redigidos em língua francesa (CPSF). O levantamento dos córpus obedeceu a critérios específicos relativos à língua, ao meio (documentos escritos), ao gênero (profissional e especializado), à autoria e à data e local de publicação, tendo sido os contratos que compuseram os córpus recolhidos de diversas fontes: principalmente virtual (sites eletrônicos de empresas, escritórios de advocacia, contabilidade), escritório de advocacia brasileiro, escritório de advocacia francês e escritório de advocacia franco-brasileiro. Do ponto de vista dos estudos terminológicos, a terminologia encontrada no contrato de prestação de serviços é composta de termos simples, termos complexos, termos ...
Keywords: Linguística; Análise linguística (Linguística); Contratos - Brasil - Terminologia; Contratos - França - Terminologia; Linguistics